SEPEDA MOTOR MODIFIKASI DALAM SENI GRAFIS - FAIZUR RAHMAN, Drs. Ariusmedi, M. Sn., Drs. Irwan, M.Sn. (Universitas Negeri Padang, 2019)
Aims to visualize modified motorbiker as things that provide social conflict in one’s own life and environment, through surrealism graphic art.In the creation of a work of art, it is necessary to carry out various preparations including making observations, information seeking, appreciation, reflection, extracting references, and literature relating to the initial idea, well as indirectly deepening the material around the environment in accordance with these problems.Through this graphic art, the author develops in form work of art, some work of art that have been exclusively presented, namely: Dreams, Stairs, Burger, Suggestion, Contamination, Trash cans, Rulers, Monsters, Lick your own saliva, and Reflection. This is the main points of things that are troubling in the life of modification.Keywords: Motorcycle Modification in Surreakism Graphic Art.